The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4028/www.scientific.net/amm.117-119.1057
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study on Microwave Absorbing Properties of SiC Absorbers

Abstract: In this paper, we have studied on the absorbing properties of three different types of SiC absorbers such as ultra-fine SiC, SiC whisker and nanometer SiC. Electromagnetic parameters of the three types of SiC were tested in the frequency range of 2~18GHz. Both the real and imaginary parts of complex permittivity of nanometer SiC are higher than that of others. The attenuation constant of nanometer SiC is higher than that of ultra-fine SiC and SiC whisker, increasing from 93.7 to 766.5 with increasing frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Besides, several studies also reported that the microwave absorbing properties of SiC increased with the decreasing of particles size. 42,43 For these reasons, SiCNWs was chosen as the microwave susceptor in this study.
Figure 5.Shear strength of the welded sample subjected to different microwave heating duration.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, several studies also reported that the microwave absorbing properties of SiC increased with the decreasing of particles size. 42,43 For these reasons, SiCNWs was chosen as the microwave susceptor in this study.
Figure 5.Shear strength of the welded sample subjected to different microwave heating duration.
…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies had shown that SiCNMs have better dielectric properties and good microwave absorption efficiency than bulk SiC. [32][33][34][35][36] Due to their improved microwave absorption at high temperature and higher dielectric loss than SiC nanoparticles, 1D-SiCNMs such as SiC nanowires and nanowhiskers have gained significant interest among SiCNMs. 37,38 For an instance, Kuang et al studied the microwave absorbing properties of SiC nanowires of various lengths.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nanomaterials had become tremendously popular for their enhanced performance owing to their high aspect ratio. Liu et al, for example examined the microwave absorbing properties of two different sized SiC, namely ultra-fine SiC (diameter <1000 nm) and nanometre SiC (diameter < 100 nm) [19]. They show that both dielectric constant and loss factor of nanometre SiC are greater than ultra-fine SiC.…”
Section: Introductionmentioning
confidence: 99%
“…SiC nanomaterials (SiCNMs) are lightweight with notable mechanical properties, high chemical and thermal stability, making them ideal microwave susceptor [20,21]. Besides, earlier research shows that the large specific surface area and interfacial polarisation of SiCNMs improved their microwave absorption performance as compared to microsized SiC [22,23]. Up to present, the use of SiCNMs as susceptor for microwave welding of thermoplastic has not yet been reported in any studies.…”
Section: Introductionmentioning
confidence: 99%